Geoscience of Climate and Energy 11. Ambient Air Quality and Linkage to Ecosystems in the Athabasca Oil Sands, Alberta - Pacey, Kevin (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2013)
SUMMARY In 2010, there were 91 active oil sands projects in the Athabasca Oil Sands, Alberta where the Wood Buffalo Environmental Association monitors air quality and related environmental impacts. In 2012, ambient air concentrations of sulphur dioxide, nitrogen dioxide, and ammonia did not exceed the Alberta Ambient Air Quality Objectives. There was one exceedance of these objectives for ground-level ozone, and 62 exceedances for fine particulate matter with aerodynamic diameter ≤ 2.5 microns. There were 170 exceedances of the 1-hour hydrogen sulphide / total reduced sulphur odour threshold. The number of hourly exceedances has decreased since 2009, yet odours remain a serious concern in some communities. Based on the Air Quality Health Index (ozone, nitrogen dioxide, fine particulate matter), the risk from ambient air quality to human health from some pollutants was calculated to be low 96% to 98% of the time depending upon monitoring location, moderate 1% to 3.4%, high ≤ 0.4%, and very high ≤ 0.2% of the year. In a highly regulated setting like the Alberta oil sands, it is critical for stakeholders to quantify the spatial influences of emission source types to explain any consequential environmental effects. Source apportionment studies successfully matched source chemical fingerprints with those measured in terrestrial lichens throughout the region. Forensic receptor modeling showed source types contributing to elemental concentrations in the lichens included combustion processes (~23%), tailing sand (~19%), haul roads and limestone (~15%), oil sand and processed materials (~15%), and a general anthropogenic urban source (~15%). Re-suspended fugitive dust from operations, tailings dikes, quarrying, on-road transportation, and land clearing was found to contribute enrichment to a much greater degree than the hitherto assumed combustion source type.